UJI AKTIVITAS ENZIM SUPEROKSIDA DISMUTASE (SOD) EKSTRAK DAUN SALAM (Syzygium polyanthum) DENGAN METODE WATER SOLUBLE TETRAZOLIUM SALT-1 (WST-1) - Fitriana Novita Sari; Ana Indrayanti; Pudiastuti Rahayu Sawarno Putri (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Free radicals can cause various kinds of degenerative diseases and skin aging. Free radicals can be neutralized with an enzymatic antioxidant, namely superoxide dismutase (SOD). One of the plants that has high SOD activity is salam (Syzygium polyanthum). The aim of this study was to determine the activity of the crude SOD extract of bay leaves precipitated with ammonium sulfate salt at various concentrations of 25, 50, 75%. The study began with plant determination, enzyme extraction, precipitation of enzyme extracts with ammonium sulfate concentrations of 25, 50, 75%, measurement of total protein content and SOD activity test using the WST-1 method to calculate the percent inhibition. The results were statistically analyzed using one way ANOVA. The results showed that the total protein content of the crude extract of SOD and the results of precipitation with ammonium sulfate 25, 50, and 75% respectively were 9.38; 6.36; 8.50; and 11.6 mg/mL. Meanwhile, the percentage inhibition values were 73.13; 34.33; 65.67; and 80.59%. The highest SOD activity was obtained in the crude extract of the enzyme precipitated with 75% ammonium sulfate salt, which was 80.59%.